Vernacular Visual Aesthetics in Homestay Design in Rural Tourism Areas of Maluku Province - Dananjaya, Ahmad Ghazy (Warna Komunikasi, 2026)
This study addresses the phenomenon of vernacular architecture marginalization in rural tourism accommodations, aiming to evaluate the influence of Local Architectural Elements (X1) and the Use of Natural Materials (X2) on Tourist Aesthetic Perception (Y) of homestays in rural Maluku. Amidst rapid modernization, preserving vernacular visual identity is crucial for maintaining a sense of place. Employing a mixed-method sequential explanatory strategy, data were collected from 199 tourist respondents using a 1-7 Likert scale questionnaire, supplemented by architectural facade visual analysis, and deepened through qualitative interviews. Multiple linear regression analysis revealed anomalous results rejecting general tourism architecture hypotheses. Tests showed that both simultaneously and partially, local architectural elements and natural materials had no significant influence on tourists' aesthetic perception (R²=0.016; Sig.>0.05). These findings indicate a shift in tourist visual preferences in Maluku, prioritizing modern functionality and visual cleanliness over poorly maintained visual authenticity. The study concludes that vernacular elements alone are insufficient to drive aesthetic preference without integration into modern standards. As an impact, this study recommends a hybrid design approach, integrating modern comfort with vernacular accents, as a new and effective visual strategy for regional tourism development.